A Taxonomic Revision of the Himalayan Junipers - Jain, K .K. (Indian Forester, 1976)
An extensive survey of the Juniperus populations in the various parts of the Himalayas was undertaken and the details of morphological as well as anatomical characters were studied to resolve the problem of the junipers complex in the Himalayas. From the entire Himalayan range eight distinct taxa or Junipers have been discovered presently. In the eastern Himalayas five taxa are present: Of these three are trees; namely J.wallichiana (sensu stricto), J.recurva (sensu stricto) and J fargesii Komarov, which are restricted to the eastern Himalayas only. The other two taxa which are shrubs, namely, J.pseudosabina Fisch. et Mey. and J.squamata Buch.-Ham. extend also to the western Himalayas. The west-Himalayan taxa also number five: Of these J.macropoda Boiss and J. excelsa Bieb. are trees, whereas the remaining three are shrubs, viz. J. communis Linn. ssp. nana Syrne, J. squamata Buch-Ham. and J. pseudosabina Fisch. et Mey. The presence of J.pseudosabina Fisch. et Mey., J.excelsa Bieb. and J.fargesii Komarov in the Indian sub-continent has been confirmed for the first time.